Spatial analysis of paddy field change in Purwakarta Regency, West Java, Indonesia - Budi Saputro; Dolly Priatna; Rosadi Rosadi; Naori Miyazawa (Universitas Pakuan, 2023)
Food is a basic human need. The state must strive to meet the availability of food for people in a sustainable manner. One of the efforts is to maintain and develop paddy fields as a food source as a supplier of 95% of national rice production. The conversion of paddy fields is a reason of decreasing of food production in Purwakarta Regency, which impact on food availability and security. This research was aimed to provide a portrait of the rate of conversion of paddy fields in Purwakarta. This research is a quantitative descriptive research using spatial analysis to compare two period of times: 2013-2017 period and the 2017-2021 period. The results of spatial analysis in the 2013-2017 period showed that Purwakarta Regency experienced a reduction in paddy fields by 195.55 ha (1%) consisting of paddy fields turned into industry 117.99 ha; roads 5.72 ha; settlements of 42.30 ha and housing, trade and services of 29.55 ha. Meanwhile, in the 2013-2017 period, paddy fields turned into industry 151.72 ha, roads by 23.54 ha, settlements 196.76 ha, and housing, trade and services 29.81 ha. The results of this study reinforce that the reduction in food production in Purwakarta was caused by the conversion of paddy fields into other uses during the 2013-2017 and 2017-2021 periods.